2023
DOI: 10.3390/birds4020015
|View full text |Cite
|
Sign up to set email alerts
|

Arabian Partridge Abundance and Limiting Factors at the Northern Boundary of Its Range

Abstract: The Arabian Partridge (Alectoris melanocephala), is an endemic bird species of the Arabian Desert that lives in groups and inhabits rocky hillsides with patchy vegetation. Throughout their range, Arabian Partridges contend with hunting and habitat destruction, factors that may limit their distribution and abundance. Although the abundance of this species has been assumed to be stable, no actual estimate of its population size has been undertaken. We assessed the distribution and estimated the abundance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For instance, feral donkeys were reported to pollute and foul water resources and prevent other native species from drinking [ 36 ]. A recent study showed that the presence of feral donkeys in the study area resulted in a ~50% decline in the number of the endemic Arabian Partridges Alectoris melanocephala [ 37 ]. In addition, feral donkeys can also facilitate disease transmission between wildlife and domestic animal [ 15 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, feral donkeys were reported to pollute and foul water resources and prevent other native species from drinking [ 36 ]. A recent study showed that the presence of feral donkeys in the study area resulted in a ~50% decline in the number of the endemic Arabian Partridges Alectoris melanocephala [ 37 ]. In addition, feral donkeys can also facilitate disease transmission between wildlife and domestic animal [ 15 , 38 ].…”
Section: Discussionmentioning
confidence: 99%